From Passive Beneficiaries to Active Agents: Exploring the Role of Rural Communities in Human Resource Development in Eastern Indonesia - Sakir, Ahmad Rosandi; Amaliah, Yusriah; Lukman, Juwita Pratiwi (Universitas Pattimura, 2024)
This study investigates the dynamics of community participation in human resource development within Barakkae Village, Lamuru District, Bone Regency, Eastern Indonesia. The primary objective is to explore the extent to which rural communities shift from being passive recipients of development initiatives to becoming active agents in shaping human capital outcomes. Employing a descriptive qualitative method, data were collected through in-depth interviews, observations, and documentation involving eight community members over the course of one month. The findings reveal a significant gap between theoretical models of participatory development and actual practice. Community involvement remains limited, particularly in decision-making processes, which are largely monopolized by village elites. This exclusion results in a lack of awareness, limited grassroots engagement, and diminished program ownership among the broader population. Additionally, the effectiveness and sustainability of human resource development programs are hindered by inadequate socialization strategies and insufficient funding. Evaluation mechanisms currently employed by village authorities also lack systematic integration of community feedback, further weakening the impact and relevance of ongoing initiatives. The novelty of this research lies in its contextual analysis of participatory barriers in a rural Indonesian setting, contributing to a deeper understanding of how local power structures and institutional limitations influence community agency. The study recommends the adoption of inclusive planning forums, the institutionalization of proposal repositories for bottom-up input, and stronger budget advocacy as pathways to reinforce local participation. These insights provide a valuable contribution to the broader discourse in social sciences and humanities by emphasizing the transformative potential of community-driven human development in peripheral regions.